Weak Near‐Field Behavior of a Tsunami Earthquake: Toward Real‐Time Identification for Local Warning - V.J. Sahakian; D. Melgar; M. Muzli (Geophysical Research Letters)
Abstract Tsunami earthquakes produce some of the most devastating tsunamis. These rare events have comparatively modest magnitudes but rupture the shallowest portion of a subduction zone megathrust with exceptionally large seafloor displacements. Previous teleseismic observations found that they radiate seismic waves weakly. They should therefore not be strongly felt in the near field, but to date no near‐source seismic recordings of these events exist that confirm this. Here we analyze near‐field records of a tsunami earthquake, the 2010 M7.7 Mentawai, Indonesia event, which show remarkably weak shaking. This is strong evidence that this earthquake does indeed have a weakly radiating or inefficient source process, in spite of its large slip. Finally, we find that, when combined with near‐source Global Navigation Satellite System displacement recordings it is possible to correctly characterize tsunami earthquakes in real‐time and to provide local tsunami warning which is currently out of reach today for monitoring agencies.